2018
DOI: 10.3390/rel9110357
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religious Behavior in Health Self-Management: A Community-Based Participatory Research Study

Abstract: Prevalence of chronic disease, mental health problems, and risk behaviors in San Bernardino (SB) County reflect some of the worst health outcomes in the State of California and the United States.Using the Integrated Theory of Health Behavior Change (ITHBC) as the theoretical framework, this community-based participatory research (CBPR) study aimed to determine how religious self-regulation skills and ability, and religious behaviors, jointly affect health promotion behaviors among socio-economically challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 75 publications
(86 reference statements)
3
20
0
Order By: Relevance
“…The result is confirmed by previous studies, which have found a negative association between religiosity [31] addictive behaviors [6,[8][9][10] and soft drink consumptions [9]. Other studies have found a positive association between spirituality and religious practice and healthy eating behaviors [12,[32][33][34]. However, this research revealed that organized, non-organized and intrinsic religiosity were not associated with healthy eating behaviors.…”
Section: Resultssupporting
confidence: 88%
“…The result is confirmed by previous studies, which have found a negative association between religiosity [31] addictive behaviors [6,[8][9][10] and soft drink consumptions [9]. Other studies have found a positive association between spirituality and religious practice and healthy eating behaviors [12,[32][33][34]. However, this research revealed that organized, non-organized and intrinsic religiosity were not associated with healthy eating behaviors.…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, one of the points that explain the relationship between religious attitudes and mental health is the feeling of hope. Pfeiffer et al., (2018) in a community‐based study on ‘The relationship between religious beliefs and actions and mental health and social function’ reported that religion influences mental health by enhancing coping with stress, creating a space for social and family support, establishing hope and happiness for positive emotions, such as a better life, life satisfaction, and happiness (Pfeiffer et al., 2018). Therefore, it can be said that hope plays the role of mental oxygen for human beings the existence of which seems necessary for survival and fighting challenges in life and this helps people to have inner determination and strong faith to face life challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Active participation and equitable partnerships in decision making are shown to improve health literacy and community wellbeing (Pfeiffer et al 2018). Trust is closely related to religious beliefs.…”
Section: Discussionmentioning
confidence: 99%